2020
DOI: 10.1080/13691058.2020.1734661
|View full text |Cite
|
Sign up to set email alerts
|

Understanding ethnic variations in HIV prevalence in Kenya: the role of cultural practices

Abstract: Patterns of HIV prevalence in Kenya suggest that areas where various cultural practices are prevalent bear a disproportionate burden of HIV. This paper examines (i) the contextual effects of cultural practices (polygyny, male circumcision) and related sexual behaviour factors on HIV prevalence and (ii) the extent to which specific cultural practices in a community/county explain existing ethnic variations in HIV prevalence in Kenya. The analysis applies multilevel logistic regression to data from the 2012/13 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have reported that intimate partner violence, household conflict, and divorce were only predominant in inter-ethnic marriages (Fryer 2007;Hohman-Marriott and Amato 2008). Encapsulating this report is the knowledge that the choice of marriage in Africa is influenced by ethnicity and cultural practices (Magadi et al 2020). In addition, the type of marriage, size of family, and practices within the family are influenced by cultural practices.…”
Section: Introductionmentioning
confidence: 66%
“…Previous studies have reported that intimate partner violence, household conflict, and divorce were only predominant in inter-ethnic marriages (Fryer 2007;Hohman-Marriott and Amato 2008). Encapsulating this report is the knowledge that the choice of marriage in Africa is influenced by ethnicity and cultural practices (Magadi et al 2020). In addition, the type of marriage, size of family, and practices within the family are influenced by cultural practices.…”
Section: Introductionmentioning
confidence: 66%
“…Polygyny is widespread in the coastal region but disproportionately distributed among counties (Magadi et al, 2020). Despite the level of modernity in Mombasa, polygyny is accepted as a form of marriage.…”
Section: Introductionmentioning
confidence: 99%